1999
DOI: 10.1002/(sici)1522-726x(199901)46:1<59::aid-ccd16>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Right coronary artery occlusion as a complication of accessory pathway ablation in a 12-year-old treated with stenting

Abstract: We describe a complication of radiofrequency ablation of a posteroseptal pathway that resulted in acute occlusion of a distal right coronary artery in a pediatric patient. The complication was treated with coronary stenting after unsuccessful angioplasty. Cathet. Cardiovasc. Intervent. 46:59–61, 1999. © 1999 Wiley‐Liss, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 11 publications
1
21
0
2
Order By: Relevance
“…These incidences concur with other published series 41,42 . Atrioventricular block may be the consequence of direct damage to atrionodal inputs or the inferior nodal extensions, 31,43,44 or trauma to the nodal artery 32,33,45 …”
Section: Discussionsupporting
confidence: 90%
“…These incidences concur with other published series 41,42 . Atrioventricular block may be the consequence of direct damage to atrionodal inputs or the inferior nodal extensions, 31,43,44 or trauma to the nodal artery 32,33,45 …”
Section: Discussionsupporting
confidence: 90%
“…3,6,[11][12][13][14][15] In a series of 18 radiofrequency ablation procedures in children weighing Ͻ15 kg, complications included pericardial effusion, mitral regurgitation, and myocardial infarction. 16 These appeared to be related to the dose of radiofrequency energy received, as indexed by body size.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported that balloon angioplasty alone does not open the artery and restore blood flow. 11,12 In these cases, the insertion of a coronary stent splints the artery open. This was the case in both of the patients in this study with acute occlusions.…”
Section: Discussionmentioning
confidence: 99%